Resource allocation for layered broadcast over relay-assisted channels - Attia, Mohamed Adel (AUC Knowledge Fountain, 2015)
The topic of this thesis is on the application of “multilayer transmission” using the broadcast approach on a “relay-assisted” channel. Unlike single layer transmission, where all transmitted information bits have the same protection level by the channel coding scheme, multilayer transmission schemes combine successive refinement layered source coding with ordered protection levels of the source layers. Consequently, the receiver will be able to decode “some” information when the channel is faded and “all” information when the channel is good. The multilayer transmission schemes have gained a lot of interest in the information theory and the communication theory literature, where most researchers are interested in the “broadcast approach” since it is the optimal transmission strategy. In this thesis, we consider a fading relay channel where the source uses layered source coding with successive refinement. The source layers are transmitted using superposition coding at the source with optimal resource allocation. The destination applies successive interference cancellation after optimally combining the direct and relayed signals. The resource allocation for the layers is subject to optimization in order to maximize the expected user satisfaction that is usually defined by a differentiable concave increasing utility function of the total decoded rate at the destination. As special cases, we consider two utility functions; namely, the expected total decoded rate at the receiver and the expected rate distortion of a Gaussian source. We also assume that only the channel statistics are known at the receiver. The relay is half-duplex and applies different relaying strategies, and we have investigated the Amplify-and-Forward, and Decode-and-Forward strategies in particular. First, we consider the case of Decode-and-Forward relays where we consider two layers only with predetermined rates for simplicity, and we solve the problem of optimal power allocation among the two layers at the source and the relay using random search methods. After that, we solve the optimal power allocation problem for any number of layers with fixed rates over an Amplify-and-Forward relays. An approximation for the end-to-end channel quality is presented in terms of the statistics of the three links of the channel model. Furthermore, we obtain that for some conditions, it is optimal to send only one layer. Finally, we solve the joint optimal power and rate allocation problem for any number of layers over an Amplify-and-Forward relays. We also consider the theoretical case of infinite number of layers representing an upper bound for the performance. Moreover, we show that with a small number of layers, we can approach the performance upper bound. We provide many numerical examples for the three cases above to show the prospected gains of using the relays on the expected utility for different channel conditions.